Pendekatan Gamifikasi Dalam Pembelajaran Al-'Adad wa Al-Ma'dud Dalam Kalangan Pelajar: The Effects of Gamification Approach to al-'Adad wa al-Ma'dud Among Students - Che Ku Mohamad, Che Ku Nor Asiah; Hassan, Abdul Rauf (Journal Al-Muqaddimah, 2020)
Al-'Adad wa al-Ma'dud is a basic Arabic grammar topic that has its own distinctive features and features. However, some studies show that the level of mastery of al-'Adad wa al-Ma'dud among students is weak. Therefore, this study aims to identify the effects of the gamification approach on the mastery of al-'Adad wa al-Ma'dud among students. For that purpose, a quasi-experimental study was conducted on 60 Form 6 students at Maahad Ahmadi, Gemencheh Negeri Sembilan. Students are divided into two groups, namely experimental groups using gamification approaches and control groups using traditional approaches. The t-test was used to analyze the data obtained. The results showed that there was no significant difference in pre-emptiness in pre-test for both approaches [t (58) =], but there were significant differences in post test [t (58) = 17.588, p <.05]. In the post test, the mean score for the experimental group is higher than the min score of the control group. This shows that the gamification approach can help students learn the al-'Adad wa al-Ma'dud topic well. This study is expected to help Arabic language educators in diversifying the Arabic language grammar and teaching techniques, especially the al-'Adad wa al-Ma'dud topic so that students can learn it more fun and meaningful.